Promoting Roles of Embryonic Signals in Embryo Implantation and Placentation in Cooperation with Endocrine and Immune Systems - Hiroshi Fujiwara; Masanori Ono; Yukiyasu Sato; Kazuhiko Imakawa; Takashi Iizuka; Kyosuke Kagami; Tomoko Fujiwara; Akihito Horie; Hirohiko Tani; Akira Hattori; Takiko Daikoku; Yoshihiko Araki (2020)
Embryo implantation in the uterus is an essential process for successful pregnancy in mammals. In general, the endocrine system induces sufficient embryo receptivity in the endometrium, where adhesion-promoting molecules increase and adhesion-inhibitory molecules decrease. Although the precise mechanisms remain unknown, it is widely accepted that maternal–embryo communications, including embryonic signals, improve the receptive ability of the sex steroid hormone-primed endometrium. The embryo may utilize repulsive forces produced by an Eph–ephrin system for its timely attachment to and subsequent invasion through the endometrial epithelial layer. Importantly, the embryonic signals are considered to act on maternal immune cells to induce immune tolerance. They also elicit local inflammation that promotes endometrial differentiation and maternal tissue remodeling during embryo implantation and placentation. Additional clarification of the immune control mechanisms by embryonic signals, such as human chorionic gonadotropin, pre-implantation factor, zona pellucida degradation products, and laeverin, will aid in the further development of immunotherapy to minimize implantation failure in the future.